Identifying sources of antibiotic resistance genes in the environment using the microbial Find, Inform, and Test framework - Wiesner-Friedman, Corinne; Beattie, Rachelle E.; Stewart, Jill R.; Hristova, Krassimira R.; Serre, Marc L. (Frontiers in Microbiology, 2023)
Antimicrobial resistance (AMR) is an increasing health concern for humans, animals, and the environment. However, contributions of spatially distributed sources of AMR in the environment are not well defined. To identify sources of environmental AMR, the novel microbial Find, Inform, and Test (FIT) model was applied to a panel of five antibiotic resistance-associated genes (ARGs), erm(B), tet(W), qnrA, sul1 and intI1, quantified from riverbed sediment and surface water from a mixed-use region. One standard-deviation-increases in modeled contributions of elevated AMR from bovine sources or land-applied waste sources [land application of biosolids, sludge and industrial wastewater (i.e., food processing), and domestic (i.e., municipal and septage)] were associated with 34-80% and 33-77% increases in relative abundances of the ARGs in riverbed sediment and surface water, respectively. Sources influenced environmental AMR at overland distances up to 13 km. Our work corroborates previous evidence of offsite migration of microbial pollution from bovine sources and newly suggests offsite migration from land-applied waste. With FIT, we estimated the distance-based influence range overland and downstream around sources to model the impact these sources may have on AMR at unsampled sites. This modeling supports targeted monitoring of AMR from sources for future exposure and risk mitigation efforts.